Fear, Antagonism, and Continuity in the Catapatha Brahmana. - Geen, Jonathan (My University, 1992)
The specific issue which prompted this study is the current controversy over the relationship between two adjacent components of Vedic Literature, namely, the brahmamas and the upanisads. Traditional Western Vedic scholarship, specifically that of the nineteenth and early twentieth centuries, vehemently insisted that the ideas found in the upanisads expressed a complete rejection of the Brahrnamic sacrificial system, which had been the dominant subject of Vedic Literature for centuries prior to the composition of the earliest upani 9ads. However, a recent study by Herman W. Tull on the Vedic origins of the Upanisadic karma doctrine has called this opinion of traditional Western Vedic scholarship into question, arguing for a large degree of continuity between the brahmanas and the upanisads . By comparing a Brahmanic discussion of a single Vedic sacrifice (i.e. the Darcapurnamaseti), with a single upanisad (i.e. the BFhadarasyaka Upanisad), this study provides evidence which furthers Tull's argument for continuity between the brahmanas and the upanisads, specifically with respect to the related issues of "fear" and "antagonism".